2008
DOI: 10.1051/forest:2007074
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of the tree-ring response of Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) to the 2003 drought and heat-wave in France

Abstract: -The genetic control of tree ring growth in Douglas-fir in response to the drought and heat-wave that occurred in 2003 in Europe was studied with microdensity profiles in three clonal experiments located in three different French regions. The drought and heat-wave significantly affected Douglas-fir wood formation. The Chassenoix site (Northeast of Massif-Central) was more severely affected that the other two: the 2003 year-ring was narrower and less dense than in the other sites and than the previous (2002) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…According to Bré da et al (2006) the first reaction of a tree to this diminution is the decrease of transpiration by stomatal closure, generally accompanied by a growth reduction. Such a significant growth reduction was observed in Douglas-fir by Martinez Meier et al (2008) in the ring formed during the year 2003, noticeably in a French site severely affected by the 2003 heat and drought wave. They also showed that this growth reduction was accompanied by a wood density decrease.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…According to Bré da et al (2006) the first reaction of a tree to this diminution is the decrease of transpiration by stomatal closure, generally accompanied by a growth reduction. Such a significant growth reduction was observed in Douglas-fir by Martinez Meier et al (2008) in the ring formed during the year 2003, noticeably in a French site severely affected by the 2003 heat and drought wave. They also showed that this growth reduction was accompanied by a wood density decrease.…”
Section: Introductionmentioning
confidence: 89%
“…They also showed that this growth reduction was accompanied by a wood density decrease. Douglas-fir was susceptible to the 2003 heat and drought wave and this response was recently found to be genetically controlled (Martinez Meier et al, 2008). But is this variation meaningful from an adaptive point of view?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few attempts have been made to use wood density as an indicator of the reaction of trees to immediate climate, and as a measure of plasticity; that is malleable by directional selection (Scheider and Lyman, 1989;Gibert et al, 2004). Recently, some authors pointed at this possibility, by showing that some microdensity variables are good indicators of extreme climate events (Rozenberg et al, 2002;Bower et al, 2005;Martinez-Meier et al, 2008), and that they seem to have significant genetic control Martinez-Meier et al, 2008).…”
Section: Consequences In Tree Breeding Programsmentioning
confidence: 98%
“…Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco), a conifer species planted abundantly in Europe and particularly in France (De Champs, 1997;Thivolle-Cazat, 2004), was strongly affected (DSF, 2004;Rozenberg and Pâques, 2004;Martinez-Meier et al, 2008). Symptoms ranged from partial foliage necrosis to individual death.…”
Section: Introductionmentioning
confidence: 98%